2023
DOI: 10.21037/jtd-22-1804
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal continuous positive airway pressure offers symptomatic benefit in excessive dynamic airway collapse despite normal sleep study

Abstract: Excessive dynamic airway collapse (EDAC) and tracheobronchomalacia (TBM) cause debilitating symptoms yet are often misdiagnosed as asthma or chronic obstructive pulmonary disease (COPD). EDAC/ TBM should be considered in all cases of obstructive ventilatory defect refractory to medical management.Diagnosis is made with flexible bronchoscopy and/or inspiratory and expiratory phase computed tomography (CT) scans. Treatment should be individualised and "pneumatic stenting" with the use of continuous positive airw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Olley et al, reported a case of EDAC managed with pneumatic stenting with nocturnal CPAP which significantly improved quality and duration of sleep, daytime symptoms and quality of life. ( 13 ) Park et al reported a case of severe EDAC managed with HFNOT as a measure of applying intermittent positive end expiratory pressure to successfully overcome the collapse of the airway, improving CO 2 retention and expectoration ( 14 ). There is an ongoing clinical trial studying the effect of CPAP on 6–minute walk test outcomes in patients with ECAC that could provide further details into the physiologic effects of pneumatic stenting ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Olley et al, reported a case of EDAC managed with pneumatic stenting with nocturnal CPAP which significantly improved quality and duration of sleep, daytime symptoms and quality of life. ( 13 ) Park et al reported a case of severe EDAC managed with HFNOT as a measure of applying intermittent positive end expiratory pressure to successfully overcome the collapse of the airway, improving CO 2 retention and expectoration ( 14 ). There is an ongoing clinical trial studying the effect of CPAP on 6–minute walk test outcomes in patients with ECAC that could provide further details into the physiologic effects of pneumatic stenting ( 15 ).…”
Section: Discussionmentioning
confidence: 99%